(untitled) (Chemical Engineering Research Bulletin, 2023)
New environmentally-friendly heat insulation materials, which are made from local raw materials can serve as an alternative to heat insulation materials already existing in the market, using clay as a raw material in its production, but dolomite is used as bio-solubility, thus obtaining material with the necessary heat and acoustic insulation qualities, as well as fire-resistance and chemical stability in an aggressive environment and providing to the development of industries in Bangladesh. Bangladesh is a developing country in the region of South Asia. Day by day its industrial growth is increasing very fast. Natural gas is used in the furnace region of all industries. It is a matter of disappointment to us that all industries never use proper insulation to save natural gas and the environment. For saving our natural gas, all industries must maintain proper furnace insulation not only for carbon emission but also for cost cost-effectiveness) of product price. Like many insulators, ceramic fiber is a key material for industrial furnace insulation. For continuous ceramic fiber fabrication, raw materials resources are important factors. In Bangladesh, raw materials are also available due to geological position. But clay raw materials are not only used as traditional raw materials but also used as heat-insulating materials. For developing ceramic fiberrelated insulation in our county, extensive study and characterization need for selecting the right clay raw materials. Characterization methods like XRF, XRD, and DSC-TG and sieve analysis give deep information about locally available clay raw materials. Chemical Engineering Research Bulletin 23 (2023): 91-96